Assessment of adolescent problems in tribal adolescent girls: a cross sectional study - Das, Swarnalata; Mishra, Sanjukta; Mohanty, Aswini Kumar; Sahoo, Soumya Sibani (International Journal Of Community Medicine And Public Health, 2017)
Background: Adolescence is a period of physical, psychological development from puberty to adulthood. There is paucity of information regarding the prevalence of behavioral, physical problems in tribal adolescents, more specifically in tribal adolescent girls, who form a different set from the mainstream section.Aim of the present study was to assess psychosocial, emotional and family life knowledge about adolescent tribal girls. Moreover it also investigated the health status and spectrum of various other problems faced by them. Methods:Sample for the study comprised of 170 tribal adolescent girls. They were selected randomly from the age group 10-19 years according to their accommodation in girl’s hostel. They were further divided into early (10-14 years) and elder (15-19 years) adolescents. Data were collected on predesigned, semi-structured questionnaire method. Study was undertaken by conducting face-to face in depth interviews of selected study population by the investigator. Data were analyzed statistically by using percentage, proportions and chi-square test. Present cross-sectional study was conducted in a tribal residential school at Bhubaneswar, Odisha. Results: Data revealed that most of tribal girls belong to low socio-economic status. Various physical problems and psychosocial problems were found to be significantly higher. Elder adolescents greatly lack information related to proper age of marriage and childbirth. Menstruation related problems and respiratory problems were found to be most prevalent in older and young group respectively. Conclusions:This gives an insight to implement adolescent friendly effective awareness programme to screen routine adolescent health problems.